The Concept of Anger Control in the Qur’anic Perspective: An Objective Study (Islamic Sciences Journal, 2023)
Suppressing anger is one of the morals of the prophets and messengers, peace and blessings be upon them, and the highest degree of self-restraint from recklessness and anger, and the most perfect types of forgiveness and quietness. The strength of faith, and this noble character personified our Messenger The Prophet, peace and blessings be upon him, and his family and peace, and the seal of the prophets. We have a good example in him, and the researcher has dealt with the issue of the concept of controlling anger in detail. Since Islam is a religion of instinct, it knows from the nature of the human soul the hesitation between truth and falsehood, so there must be limits and controls in which the soul controls the individual’s entity in order to balance between them.  And Islam has regarded this instinct that created people and did not abandon it, but rather refined it and made it equivalent to his law, proceeding according to his principles, so anger can turn into  pardon, tolerance and patience.